2005
DOI: 10.1038/sj.mp.4001687
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-mediated knockdown of the serotonin transporter in the adult mouse brain

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are widely used antidepressant drugs that increase the extracellular levels of serotonin by blocking the reuptake activity of the serotonin transporter (SERT). Although SSRIs elevate brain serotonergic neurotransmission acutely, their full therapeutic effects involve neurochemical adaptations that emerge following chronic drug administration. The adaptive downregulation of SERT has recently been implicated in the therapeutic response of SSRIs. Interestingly, stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(74 citation statements)
references
References 36 publications
8
66
0
Order By: Relevance
“…45−47 For example, a 30% decrease in striatal tyrosine hydroxylase was sufficient to reduce the hyperactive locomotor response to amphetamine in mice 46 and antidepressant-like behaviors were observed in mice, after icv infusion of siRNA led to a 40% reduction in expression of the serotonin transporter. 47 In summary, an amphiphilic cationic modified β-cyclodextrin was shown to deliver siRNA to neurons for gene silencing. Efficient uptake into neuronal cells was shown, with a favorable cytotoxicity profile.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…45−47 For example, a 30% decrease in striatal tyrosine hydroxylase was sufficient to reduce the hyperactive locomotor response to amphetamine in mice 46 and antidepressant-like behaviors were observed in mice, after icv infusion of siRNA led to a 40% reduction in expression of the serotonin transporter. 47 In summary, an amphiphilic cationic modified β-cyclodextrin was shown to deliver siRNA to neurons for gene silencing. Efficient uptake into neuronal cells was shown, with a favorable cytotoxicity profile.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The mRNA-induced 5-HT uptake was measured in transport assays, and the effect of PMAT-specific antisense oligos was investigated. To ensure specificity, we included sense oligos as controls and designed both PMAT and SERT oligos based on sequences that were shown to be effective and specific in previous RNAi studies [12,22]. Our results showed that pre-hybridization of total human brain poly(A) + mRNA with PMAT antisense substantially reduced mRNA-induced 5-HT uptake, suggesting that functional PMAT transcripts are present in the human brain, and PMAT may be significantly involved in total brain uptake of 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…At clinically encountered concentrations in the brain (low nanomolar range) (Table 3) Illustration of positions of PMAT and SERT oligos used in hybrid depletion study. * values are calculated as steady state plasma concentrations of total drug times plasma unbound fraction using data from [22,23], assuming that unbound brain concentrations of SSRIs approximate their unbound plasma concentrations [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon local multidosal administration, naked unmodified siRNA silences target gene expression in the lung, the eye or the central nervous system. [4][5][6] Systemic applications of RNAi, in contrast, are hampered by rapid degradation and renal excretion. 2 To improve systemic delivery, siRNA delivery vehicles based on conjugates, liposomes or nanoparticles are being developed.…”
Section: Introductionmentioning
confidence: 99%